(untitled) (Studia Prawnicze / The Legal Studies, 2023)
Wraz z wejściem w życie kodeksu cywilnego z 1964 r. wątpliwości dotyczące kwestii winy poszkodowanego nie zostały całkowicie rozwiązane. Wina poszkodowanego spełnia w polskim porządku prawnym różnorodne funkcje. Występuje między innymi jako okoliczność zwalniająca od odpowiedzialności na zasadzie ryzyka czy może zmienić zakres odpowiedzialności sprawcy, np. zmniejszając odszkodowanie zgodnie z brzmieniem art. 362 k.c. Autor artykułu próbuje scharakteryzować pojęcie winy poszkodowanego w polskim prawie cywilnym opierając się na dokonaniach doktryny w tej materii, wykładni przepisów kodeksu cywilnego oraz judykaturze. With the entry into force of the 1964 Civil Code, doubts regarding the issue of the injured party’s fault were not completely resolved. The fault of the injured party fulfils various functions in the Polish legal order. Among other things, it occurs as a circumstance exempting strict liability or may alter the extent of the perpetrator’s liability, e.g. by reducing damages in accordance with the wording of Article 362 of the Civil Code. The author of this article attempts to characterise the concept of the injured party’s fault in Polish civil law, drawing on the achievements of the doctrine in this area, the interpretation of the provisions of the Civil Code and the jurisprudence.